Investigating the Qiroati Methods’s Effect on Tajweed Undesrtanding among the Fourth Graders - Fitriani, Rizkha; Sunarso, Ali (Edukasi, 2025)
This study aimed to analyze the understanding of Tajweed among grade VI students at SD IT Al Mawaddah Semarang through the application of the Qiroati method and its impact on improving their Qur'anic reading skills, particularly in terms of fluency, pronunciation accuracy, and correct application of Tajweed rules.. The research used a qualitative approach with a case study. The research subjects consisted of thirty students of grade VI and two Qur'anic supervisors. Data collection techniques included in-depth interviews, observation of the teaching and learning process, and documentation of student reading results. Data analysis were carried out using the Miles and Huberman model, through the stages of data reduction, data presentation, and conclusion/verification. The findings of the study showed that the Qiroati method is effective in improving the skill of reading the Qur'an with the rules of tajweed, although obstacles such as the influence of local dialects and difficulties in distinguishing the makhraj of similar letters are still found. The Qiroati method had been proven to significantly improve students' Qur'an reading techniques if supported by a variety of teaching methods and improving the quality of teachers. Therefore, it is recommended that schools optimize the use of creative learning media and pay attention to the individual learning needs of students to achieve more optimal learning outcomes.